2020
DOI: 10.1101/2020.06.17.157917
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The mechanisms behind perivascular fluid flow

Abstract: Flow of cerebrospinal fluid (CSF) in perivascular spaces (PVS) is one of the key concepts involved in theories concerning clearance from the brain. Experimental studies have demonstrated both net and oscillatory movement of microspheres in PVS (Mestre et al. (2018), Bedussi et al. (2018)). The oscillatory particle movement has a clear cardiac component, while the mechanisms involved in net movement remain disputed. Using computational fluid dynamics, we computed the CSF velocity and pressure in a PVS surroundi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…We let the flow be driven by a constant pressure gradient ∂p ∂z = 1.46 mmHg/m. Even though such a gradient has only been reported as a pulsatile gradient [25], static gradients of this magnitude have been shown to create net velocities of around 20 µm/s in the PVS [16] in agreement with experimental observations of injected microspheres in pial PVS. We also conducted experiments with a lower pressure gradient: ∂p ∂z = 0.01 mmHg/m [25] corresponding to the third circulation's production of CSF alone [26].…”
Section: A) B)supporting
confidence: 83%
See 2 more Smart Citations
“…We let the flow be driven by a constant pressure gradient ∂p ∂z = 1.46 mmHg/m. Even though such a gradient has only been reported as a pulsatile gradient [25], static gradients of this magnitude have been shown to create net velocities of around 20 µm/s in the PVS [16] in agreement with experimental observations of injected microspheres in pial PVS. We also conducted experiments with a lower pressure gradient: ∂p ∂z = 0.01 mmHg/m [25] corresponding to the third circulation's production of CSF alone [26].…”
Section: A) B)supporting
confidence: 83%
“…Local arterial wall pulsations can induce a small net flow, of 0.1 µm/s over a 5 mm long PVS or up to 7 µm/s in very long (100 mm) PVSs [16]. On the other hand, tracer infusions increase the intracranial pressure (ICP) [11], and may also give rise to a small but longlasting ICP gradient [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterizing the flow, however, is easier than determining its driver. Although arterial pulsation has long been considered as a possible driving mechanism for the bulk flow (Bilston et al, 2003;Hadaczek et al, 2006;Wang and Olbricht, 2011;Iliff et al, 2013;Thomas, 2019;Daversin-Catty et al, 2020), that notion remains controversial (Diem et al, 2017;Kedarasetti et al, 2020a;van Veluw et al, 2020), and other mechanisms are possible.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical modeling is therefore a compelling tool to investigate CSF/IFS-exchange related to brain clearance or drug delivery. Computational studies [11][12][13] investigating CSF flow in paravascular spaces (PVS) have not been able to reproduce the average flow velocities reported in experimental studies with microspheres. 14,15 Within the interstitium, both experimental, 7 and computational 16 studies have concluded that diffusion dominates convection.…”
Section: Introductionmentioning
confidence: 99%